Non-steroidal anti-inflammatory drugs in the watercourses of Elbe basin in Czech Republic - Marsik, Petr; Rezek, Jan; Židková, Monika; Kramulová, Barbora; Tauchen, Jan; Vaněk, Tomáš (Chemosphere, 2017)
Non-steroidal anti-inflammatory drugs (NSAIDs) belong to most used pharmaceuticals in the human and veterinary medicine. The widespread consumption of NSAIDs has led to their ubiquitous occurrence in water environment including large river systems. In the present study, concentrations of the five most frequently used NSAIDs (ibuprofen, diclofenac, naproxen, ketoprofen and indomethacin) were determined in the watercourses of the river Elbe basin in Czech Republic. The presence of the pharmaceuticals was measured at 29 sampling sites including urban and rural areas, small creeks and main tributaries of the Elbe monthly from April to December of 2011. For the NSAIDs quantitation, the comprehensive analytical method combing pentafluorobenzyl bromide (PFBBr) derivatization with highly sensitive two-dimensional gas chromatography time-of-flight mass spectrometry (GCxGC-TOFMS) was developed. Although the content of all NSAIDs varied at the particular sampling points significantly, total amount of particular compounds was relatively stable during all monitored periods with only non-significant increase in the spring and autumnal months. Ibuprofen was found to be the most abundant drug with maximum concentration of 3210 ng/L, followed by naproxen, diclofenac and ketoprofen (1423.8 ng/L, 1080 ng/L and 929.8 ng/L, respectively). Indomethacin was found only at several sampling sites (maximum concentration of 69.3 ng/L). Concentrations of all compounds except ibuprofen were significantly higher at sampling sites with low flow rates (creeks), followed by the biggest watercourses.
Keywords: ibuprofen; chemické látky znečišťující vodu; Environmental Monitoring; Elbe basin; Naproxen; NSAID; monitorování životního prostředí; GCxGC-TOFMS; Česká republika; řeky; Diclofenac; plynová chromatografie s hmotnostně spektrometrickou detekcí; Indomethacin; Water Pollutants, Chemical; Rivers; Ketoprofen; Gas Chromatography-Mass Spectrometry; Anti-Inflammatory Agents, Non-Steroidal; Czech Republic; antiflogistika nesteroidní; Surface water; Ibuprofen; diklofenak; Pharmaceuticals; indomethacin; ketoprofen; naproxen